Teaching Performance: The Consequences of Burnout and Its Relation to Protective Factors - Prieto-Molinari, Diego E. (2023)
The burnout syndrome is an occupational health indicator that intervenes in the teaching-learning process and may harm the quality of education offered by institutions. The relationship between individual characteristics and the work environment may have different effects over the teaching performance. The current investigation seeks to analyze the fit of a model to predict teaching performance based on the teacher burnout, while including individual characteristics and the work environment perception in university teachers. The sample is composed of 94 teachers who provided information related to the Conscientiousness trait, their burnout and engagement levels, their teaching performance, and their perception of the work environment. This quantitative and cross-sectional research makes use of structural equation models to test its hypothesis. The second tested model showed the best fit, considering teaching performance as different variables for each component. This model shows that the perception of the work environment is the main predictor of performance (β = .116 - .239). The implications of these findings are discussed, focusing specially on performance as a construct.